Respostas

2013-11-12T23:56:01-02:00
Bem resolução de sistemas:
A)  x-2y=0 x (-2)
     2x-5y=3

    -2x+4y=0                x-2y=0
     2x-5y=3                x-2(-1)=0       
       -y=3 x (-1)            x+2=0
          y=-1                  x=-2

B) x+y=5                x+y=5
    2x-y=9               14/3+y=5
      3x=14                 y=5-14/3 (tirar M.M.C.)
        x=14/3              y= 15/3 - 14/3
                                y=1/3
2013-11-13T00:45:47-02:00
A) Se x=2y

substitui na segunda  2x - 5y = 3

2*(2y) - 5y = 3   → 4y - 5y = 3 → -y = 3

B)  x+y = 5 → y = 5 - x substitui na segunda

2x-y=9  → 2x - (5 - x) = 9 → 2x - 5 + x = 9

3x = 9 + 5 → 3x = 14 → x = 14/3